Gene Therapy: Novel Approaches to Targeting Monogenic Epilepsies - Goodspeed, Kimberly; Bailey, Rachel M.; Prasad, Suyash; Sadhu, Chanchal; Cardenas, Jessica A.; Holmay, Mary; Bilder, Deborah A.; Minassian, Berge A. (Frontiers in Neurology, 2022)
Genetic epilepsies are a spectrum of disorders characterized by spontaneous and recurrent seizures that can arise from an array of inherited or de novo genetic variants and disrupt normal brain development or neuronal connectivity and function. Genetically determined epilepsies, many of which are due to monogenic pathogenic variants, can result in early mortality and may present in isolation or be accompanied by neurodevelopmental disability. Despite the availability of more than 20 antiseizure medications, many patients with epilepsy fail to achieve seizure control with current therapies. Patients with refractory epilepsy—particularly of childhood onset—experience increased risk for severe disability and premature death. Further, available medications inadequately address the comorbid developmental disability. The advent of next-generation gene sequencing has uncovered genetic etiologies and revolutionized diagnostic practices for many epilepsies. Advances in the field of gene therapy also present the opportunity to address the underlying mechanism of monogenic epilepsies, many of which have only recently been described due to advances in precision medicine and biology. To bring precision medicine and genetic therapies closer to clinical applications, experimental animal models are needed that replicate human disease and reflect the complexities of these disorders. Additionally, identifying and characterizing clinical phenotypes, natural disease course, and meaningful outcome measures from epileptic and neurodevelopmental perspectives are necessary to evaluate therapies in clinical studies. Here, we discuss the range of genetically determined epilepsies, the existing challenges to effective clinical management, and the potential role gene therapy may play in transforming treatment options available for these conditions.